Employment (UN New YorkUS, 2000)
Points out that employment promotion is a major goal pursued by governments and that transnational corporations (TNCs) have an employment-generating potential that can be harnessed. Illustrates how such issues as the right of association, collective bargaining and consultation can be dealt with in an international investment agreement (IIA). Examines certain emerging issues, including TNC specific IIA provisions to cover all core labour standards and efforts to ensure observance of such provisions through a social clause.
Keywords: EMPLOYMENT